The Art of Inclusion: Tactics in reaching communities for participatory design - Wildan Aulia; Imam Santosa; Muhammad Ihsan DRSAS; Adhi Nugraha (Jurnal Desain Indonesia., 2025)
This article delves into the practical strategies employed to engage communities effectively in participatory design, utilizing a systematic literature review (SLR) methodology drawing from Scopus and ScienceDirect databases. Analyzing 14 selected articles and incorporating an additional five, we identified explicit statements addressing challenges and strategies while exploring implicit insights into community engagement approaches. Thematic analysis categorized eight challenging areas for designers: community heterogeneity, age groups, gender and priority segments, economic and social factors, physical environment, education and literacy, cultural nuances, and mental/physical health. The insights gained emphasize the importance of adaptable and inclusive approaches for designers involved in participatory design. The review signifies the need for skill development, highlighting flexibility and inclusivity as pivotal factors when choosing approaches.